PRE-ANESTHETIC MEDICATIONS IN PATIENTS UNDERGOING EXPLORATORY LAPAROTOMY: RESULTS OF A CROSS-SECTIONAL STUDY - Patil, Anant; Kulkarni, Madhuri (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: The objective of this study was to understand the pattern of pre-anesthetic medication utilization in patients undergoing exploratory laparotomy. Methods: In this cross-sectional study, we reviewed the records of patients who underwent exploratory laparotomy under general anesthesia. Descriptive data of the pre-anesthetic medications used in the patients are presented. Results: A total of 49 patients with mean age of 65.85Â±34.15 years were included in the study. The study population was dominated by male patients (65.85%). Two major indications for exploratory laparotomy in the study population were perforation peritonitis 19 (38.77%) and intestinal obstruction 9 (18.37%). Ondansetron was used in all patients. metoclopramide and ranitidine were used in 48 (98%) patients each. Midazolam was given to 43 (87.8%) patients. A total of 41 (83.7%) patients received anticholinergic agent glycopyrrolate or atropine. Pentazocine and fentanyl were used in 39 (79.6%) and 10 (20.4%) patients, respectively. Conclusion: Ondansetron, metoclopramide, ranitidine, midazolam, glycopyrrolate, and pentazocine were the major pre-anesthetic medications in patients undergoing exploratory laparotomy. Glycopyrrolate was the most preferred anticholinergic agent.